Characterization of Class F Fly Ash Using STXM: Identifying Intraparticle Heterogeneity at Nanometer Scale. (16th March 2016) - Ha, J.; Chae, S.; Chou, K. W.; Tyliszczak, T.; Monteiro, P. J. M.
Abstract : Chemical and physical characterization of fly ash particles were conducted using scanning transmission X-ray microscopy (STXM). Compositional and spatial investigation and correlation among the main elemental constituents of fly ash (Al, Si, and Fe) were conducted based on microscopic and NEXAFS spectral analysis. Homogeneous oxidation and coordination state of Al and Fe were observed whereas Si shows spatial variation in its chemical state. We also identified that Si and Al are spatially correlated at nanometer scale in which high concentration of Si and Al was concurrently and consistently observed within the 30 nm resolution whereas Fe distribution did not show any specific correlation to Al and Si. Results of this study indicate that fly ash chemical composition has heterogeneous distribution depending on the elements which would determine and result in the differences in the reactivity.